In silico and two-hybrid functional characterization of the Rhipicephalus microplus (Canestrini, 1888) vaccine antigen Bm86 - Maritz-Olivier, Christine (University of Pretoria, 2024)
Dissertation (MSc (Genetics))--University of Pretoria, 2020.